2022
DOI: 10.1007/s00894-022-05186-9
|View full text |Cite
|
Sign up to set email alerts
|

First-principles study of strain on BN-doped arsenene

Abstract: The effects of B, N, and BN doped arsenenes and different strains on the optoelectronic properties of BN doped arsenene were investigated using a rst-principles approach. The B, N, and BN doping caused the bandgap of arsenene to shift from indirect-direct and a strong charge-transfer occurred between arsenene and B, N and BN, and the transfer between N atoms and arsenene was more drastic. The structural stability and bandgap decrease gradually with the increase of tensile and compressive deformation, but the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The effect of strain on each key parameter of the F-atom doped SnS 2 structure is realized by changing the lattice constant of the material, as shown in figure 2. The equation describing the magnitude of strain is depicted as [30]: ε = (a -a 0 ) / a 0 × 100%, where a 0 and a are the optimized lattice parameters of the doped system before and after applying the strain on the x-axis and the y-axis, respectively, which corresponds to the decreases and increases of the lattice constants of compressive and tensile strains. In selecting the strain range, considering the stability of the structure, a strain of −9% to 9% is applied to the doped system in both X and Y axes (+ and -denote the applied tensile and compressive strains, respectively).…”
Section: Modeling and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of strain on each key parameter of the F-atom doped SnS 2 structure is realized by changing the lattice constant of the material, as shown in figure 2. The equation describing the magnitude of strain is depicted as [30]: ε = (a -a 0 ) / a 0 × 100%, where a 0 and a are the optimized lattice parameters of the doped system before and after applying the strain on the x-axis and the y-axis, respectively, which corresponds to the decreases and increases of the lattice constants of compressive and tensile strains. In selecting the strain range, considering the stability of the structure, a strain of −9% to 9% is applied to the doped system in both X and Y axes (+ and -denote the applied tensile and compressive strains, respectively).…”
Section: Modeling and Methodologymentioning
confidence: 99%
“…the total energy of the F-doped defective SnS2 system, E S S sv n 2 -denotes the total energy of the vacancy-deficient SnS2 system, E s denotes the energy of a single S atom, E f denotes the energy of one of the F atoms doped, and n denotes the number of atoms where substitutional doping occurs. The formula for the binding energy of the doped system under different strains is defined as [33]:…”
Section: Modeling and Methodologymentioning
confidence: 99%
“…Finally, the main group dopants like Al, Ga, In, As, and Sb have also been proposed as valuable dopants for germanene. [33][34][35] Shiraz et al [33] concluded that Al, Ga, and In induce a p-type semiconductor character, while P, As, and Sb are n-type. Nevertheless, the intrinsic behavior of germanene remains unchanged when Si and Sn are introduced are introduced in the germanene framework.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, strong charge transfers occurred between B, N, BN, and arsenene. Among them, the transfer between the N atom and arsenene was the strongest [39]. Wu et al discovered that the O 2 molecule is more prone to chemical adsorption in a TM-doped arsenene system with higher adsorption energy than in an ideal arsenene system.…”
Section: Introductionmentioning
confidence: 99%